Pelatihan Pembuatan Briket Dari Limbah Cangkang Kemiri - Loth Botahala; Adolfina Oualeng; Herlince Padamakani; Dusse E. Botahala (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Global warming is a process of increasing the average temperature in the atmosphere, at sea, and on land, so that it will result in very extreme climate changes on earth. One of the exhaust gases known by various levels of society is carbon dioxide gas or commonly abbreviated as CO2. This gas is formed due to various human activities and because it occurs naturally, including burning garbage to forest fires. The candlenut shell is a waste from the candlenut fruit which has become a new problem in the community, especially the residents of the candlenut-producing villages. This community service aims to educate about the improtance of preserving forests and practice of making briquettes from to candlenut shell waste as fuel to replace  for household purposes. The participants have understood that processing candlenut shell waste into briquettes as a substitute for fuel can reduce the action of deforestation so that it indirectly already supports the function of the forest as the lungs of the earth.